The effect of modified heat moisture treatment with microwave on physicochemical characteristics of sago starch - Santoso, Sugeng; Polnaya, Febby J.; Picauly, Priscillia (AGROMIX, 2024)
Introduction: This study aimed to characterize the physicochemical properties of forage sago starch using a microwave with different moisture content, namely 20%, 25%, and 30%. Method: A randomized non-factorial design was used with four treatment levels, namely native starch, HMTMW20, HMTMW25, and HMTMW30. Furthermore, the analyzed parameters were moisture and ash content, water and oil absorption, swelling power, and solubility. Result: The results showed that moisture content of forages (9.35-12.20%) was lower than native starch (13.08%), ash content of sago starch forages (0.15-0.23%) was lower than native sago starch (0.30%), water absorption of HMTMW sago starch (216.19-317.47%) was higher than native sago starch (222.07%). Furthermore, the absorption of HMTMW sago starch oil (189.73-208.40%) was higher than native starch (176.53%), swelling power value of HMTMW sago starch (23.33-31.90%) was relatively lower than native sago starch (33.07%), solubility of HMTMW sago starch (12, 38-18.47%) was relatively lower than native sago starch (21.00%). Conclusion: HMTMW with different initial moisture content (20, 25, and 30%) using 40% power for 15 minutes caused changes in the physicochemical properties of sago starch. In addition, higher concentrations of the initial treatment caused an increase in moisture content and water and oil absorption, while ash content, swelling power, and solubility decreased.